Associations between physical function, dual-task performance and cognition in patients with mild Alzheimer's disease. (1st November 2016) - Sobol, Nanna Aue; Hoffmann, Kristine; Vogel, Asmus; Lolk, Annette; Gottrup, Hanne; Høgh, Peter; Hasselbalch, Steen G.; Beyer, Nina
Abstract : Objective: Alzheimer's disease (AD) causes a gradual decline in cognition, limitations of dual-tasking and physical function leading to total dependence. Hence, information about the interaction between physical function, dual-task performance and cognition may lead to new treatment strategies with the purpose of preserving function and quality of life. The objective of this study was to investigate the associations between physical function, dual-task performance and cognition in community-dwelling patients with mild AD. Methods: Baseline results from 185 participants (50–90 years old) in the single blinded multicenter RCT 'ADEX' (Alzheimer's disease: the effect of physical exercise) were used. Assessments included tests of physical function: 400-m walk test, 10-m walk test, Timed Up and Go test and 30-s chair stand test; dual-task performance, i.e., 10-m walk while counting backwards from 50 or naming the months backwards; and cognition, i.e., Mini Mental State Examination, Symbol Digit Modalities Test, the Stroop Color and Word Test, and Lexical verbal fluency test. Results: Results in the 30-s chair stand test correlated significantly with all tests of cognition ( r = .208–.242) while the other physical function tests only randomly correlated with tests of cognition. Results in the dual-task counting backwards correlated significantly with results in all tests of cognition ( r = .259–.388), which accounted for 7%–15% of the variation indicating that a faster time to complete dual-task performance was associated with better cognitive performance. Conclusion: The evidence of the associations between physical function, dual-task performance and cognition is important when creating new rehabilitation interventions to patients with mild AD.